Efficiency of Drug Inventory Control in Hospitals in Indonesia Using the Minimum-Maximum Stock Level: A Systematic Review - Putu Hediarta Widiana Putra; Satibi Satibi; Susi Ari Kristina (Faculty of Pharmacy, Universitas Gadjah Mada, 2026)
Background: Efficient drug inventory management in hospitals is crucial for ensuring the availability of necessary medications while avoiding excessive costs and storage challenges. In developing countries, pharmaceuticals account for 40–50% of total hospital expenditures, highlighting the importance of inventory control. The Minimum-Maximum Stock Level (MMSL) method is a straightforward approach to managing hospital drug inventory that prevents overstocking and causes reorders to avoid shortages.Objectives: This study aims to evaluate the impact of the MMSL method on drug inventory control efficiency in hospitals in Indonesia.Methods: This systematic review was conducted following the PRISMA Statement guidelines. Articles were identified from PubMed, Scopus, Garuda, and Google Scholar databases. Studies conducted in hospitals in Indonesia that evaluated the implementation of the MMSL and reported efficiency indicators such as inventory value, Inventory Turnover Ratio (ITOR), stockout, and dead stock were included. The methodological quality of the selected studies was assessed using the JBI critical appraisal tools.Results: A total of seven reviewed articles showed that the MMSL method positively influenced the efficiency of drug inventory control in hospitals, as evidenced by reductions in drug inventory values, increases in ITOR, decreases in stockout frequency and value, and a reduction in dead stock. In another study, ITOR decreased at a government hospital, although it remained within the ideal value range.Conclusion: The MMSL method enhances the efficiency of drug inventory management and can be implemented in hospitals in Indonesia.